How to Survey the Emerging Polish Upper Class – Questions, Dilemmas, Reflections - Bombol, Małgorzata (Warsaw Forum of Economic Sociology, 2015)
In light of the significant stratification of Polish middle class, the formation of a group of people representing the ’seed’ Polish upper class seems to be obvious. This is a group almost totally unrecognized by economic sciences, though representing a very important segment of customers. The difficulties in the recognition of the group are not only the consequence of the lack of developmental analogies to other market economies (almost 60-yearlong break in functioning of this class in Poland), but also its hermetic nature. The paper will also present the major dilemmas encountered by the authoress at the stage of carrying out her research surveys.